Integrated airside landside framework to assess passenger missed connections with airport departure metering - Ali, Hasnain (2022)
Airport departure metering can contain airside congestion but it may adversely impact scheduled gate assignments leading to passenger missed connections. Using an integrated landside airside framework, this study aims at evaluating the impact of departure metering on connecting flights and passenger connections. The proposed framework comprises of landside and airside simulators where the landside simulator simulates transfer passenger movements conditioned upon minimum connection time and the airside simulator simulates runway and taxiway movements based on planned operations and available data source. Departing aircraft movements are then metered to reduce taxi and take-off delays under uncertainties. Delayed arrivals and/or departures may lead to conflicts at gate rendering planned gate assignments infeasible or impractical. Using Singapore Changi airport A-SMGCS data, as a case study, it is found that DM may transfer as much as 12 minutes of waiting time from taxiways to gates. This leads to increased gate conflicts which additionally delays the gate-in time of an arriving aircraft by 2-7 minutes on average. Gate reassignments were found to significantly reduce both the number of gate conflicts and arrival queuing time at gates leading to less passenger delays. A minimum connection time of 70 minutes is found sufficient to reduce the probability of missed connections for transfer passengers.